Synthesis of functionalized 2,5-dihydro-1,2-oxaphospholes via one-pot three-component reaction - Balalaie, Saeed; Baoosi, Leila; Tahoori, Fatemeh; Rominger, Frank; Bijanzadeh, Hamid Reza (Journal of the Iranian Chemical Society, 2015)
An efficient one-pot synthesis of novel 2,5-dihydro-1,2-oxaphosphole derivatives via a three-component reaction of triphenyl phosphine, dialkyl acetylenedicarboxylates, and methyl (arylmethylidene) pyruvates has been reported. Carrying out the reaction in mild reaction conditions and synthesis of functionalized oxaphospholes are advantages of this approach.
Published online: 20 May 2014
Gesehen am 29.07.2020